A comparison of the concentration‐effect relationships of midazolam for EEG‐derived parameters and saccadic peak velocity - Steveninck, AL; Mandema, JW; Tuk, B; Dijk, JG; Schoemaker, HC; Danhof, M; Cohen, AF (British journal of clinical pharmacology, 1993)
1. Concentration‐effect relationships of midazolam were assessed in an open study in six healthy volunteers. Saccadic eye movements and EEG parameters derived by fast Fourier transform (FFT) and aperiodic analysis (AP) were used to quantify drug effects. 2. Midazolam was infused at a rate of 0.6 mg kg‐1 h‐1 for a maximum of 15 min. Hypnotic effects were avoided by terminating infusions when subjects could no longer perform the eye movement test properly. 3. Wake‐sleep transitions could be recognized through frequent observation of eye movements. The dose needed to reach maximum conscious sedation averaged 0.10 mg kg‐1, ranging from 0.06 to 0.13 mg kg‐1. 4. Sigmoidal concentration‐effect relationships were found for EEG beta‐amplitudes in five of six subjects, with average EC50 values (+/‐ s.d.) of 120 +/‐ 54 ng ml‐1 for FFT and 104 +/‐ 40 ng ml‐1 for AP. For the 'total number of waves' in the beta frequency range (AP) an average (n = 6) EC50 of 63 +/‐ 37 ng ml‐1 was found. Changes in EEG alpha‐amplitudes were found in three subjects, resulting in an average EC50 value of 55 +/‐ 32 ng ml‐1. 5. For saccadic peak velocity (PV) concentration‐effect relationships were linear in five subjects and sigmoidal in one. The maximal measured decrease in PV averaged ‐44 +/‐ 9%. 6. The differences in concentration‐effect relationships for various effect parameters call for further studies with emphasis on the external validity and reproducibility of data. In such studies the dose needed to reach wake‐ sleep transition may be used as a relevant clinical end‐point.